Unlocking Drug Delivery Potential: The Crucial Role of Liposome Mechanical Properties - Gregoria (BULETIN FISIKA, 2026)
The mechanical properties of liposomes play a critical role in determining their stability, drug release behavior, biodistribution, and interaction with biological barriers. These properties are primarily governed by lipid composition, including the degree of acyl chain saturation, tail length, and headgroup charge. Cholesterol incorporation is a widely used strategy to increase membrane rigidity by condensing the bilayer and reducing permeability. Temperature also modulates mechanical behavior, with liposomes transitioning from a rigid gel phase below the lipid phase transition temperature to a more fluid and permeable liquid-crystalline phase above it. Structural features such as liposome size and lamellarity further influence mechanical performance, larger liposomes tend to be more flexible, whereas multilamellar vesicles exhibit greater stiffness. Precisely controlling liposome stiffness through careful manipulation of their mechanical properties is a fundamental design principle for creating more effective nanocarriers in cancer therapy. Achieving moderate liposome stiffness is particularly advantageous, as it can result in extended circulation within the bloodstream and enhanced accumulation within tumors by exploiting the enhanced permeability and retention effect.